2012
DOI: 10.1093/wbro/lks009
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Health Insurance Schemes for the Informal Sector in Low- and Middle-Income Countries: A Systematic Review

Abstract: This paper summarizes the literature on the impact of state subsidized or social health insurance schemes that have been offered, mostly on a voluntary basis, to the informal sector in low-and middle-income countries. A substantial number of papers provide estimations of average treatment on the treated effect for insured persons. We summarize papers that correct for the problem of self-selection into insurance and papers that estimate the average intention to treat effect. Summarizing the literature was diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
170
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(181 citation statements)
references
References 44 publications
9
170
2
Order By: Relevance
“…It has been shown that the cost of major illness may lead to impoverishment (see, among others, Wagstaff [2007] and Wagstaff and van Doorslaer [2003]). This is particularly the case for the most vulnerable categories in society; workers in the informal sector and rural areas are less likely to be involved in mandatory social security schemes, as is often the case for public servants and workers in the formal private sector (see Acharya et al [2013] and Ekman [2004] for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the cost of major illness may lead to impoverishment (see, among others, Wagstaff [2007] and Wagstaff and van Doorslaer [2003]). This is particularly the case for the most vulnerable categories in society; workers in the informal sector and rural areas are less likely to be involved in mandatory social security schemes, as is often the case for public servants and workers in the formal private sector (see Acharya et al [2013] and Ekman [2004] for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…Based on our findings, morbidity patterns and outpatient care were similar up until the point of hospitalisation – but there is no indication of whether higher inpatient admission results in better long term health. Thus far, evaluations of CBHI as well as larger social insurance schemes have focused on the quantitative increase in utilisation and financial security afforded by coverage, with limited assessment of the associated effects on health [2,3,12]. Encouragingly, a recent study in Burkina Faso has investigated the association of CBHI coverage with mortality outcomes [45].…”
Section: Resultsmentioning
confidence: 99%
“…According to findings from a systematic review in 2009 that covered 31 studies and 118 schemes, and an earlier review of 12 schemes in Asia and Africa, there is strong evidence that CBHI schemes can decrease out of pocket spending on health care [2,3] A large proportion of schemes in low-income settings cover only inpatient hospitalisation expenses, and CBHI coverage has been associated with increased hospitalisation in a number of studies [4-9]. However, health systems issues such as poor quality of services and lack of patient empowerment remain barriers to increased treatment-seeking [10,11], while low enrolment limits coverage of CBHIs and similar voluntary schemes [12]. Despite these weaknesses, CBHIs continue to be implemented in many low-income countries, as a potential tool to improve access and financial security [1].…”
Section: Introductionmentioning
confidence: 99%
“…Given the large share of OOP payments in health care in India, RSBY is considered a very innovative scheme that relies on providing cashless health services to the beneficiary households without any paperwork with the use of smart cards (more details are provided in section 1.1) with only a marginal enrollment/renewal cost of 30 Indian Rupees (INR) (about $0.5) per year. 1 It covers up to five members of family. As of November, 2012, 33.19 million 1 The World Bank hailed RSBY as a model of good design and implementation with important lessons for other programs in India.…”
Section: Introductionmentioning
confidence: 99%
“…1 It covers up to five members of family. As of November, 2012, 33.19 million 1 The World Bank hailed RSBY as a model of good design and implementation with important lessons for other programs in India. http://pib.nic.in/newsite/efeatures.aspx?relid=69262 1 BPL families were enrolled in RSBY, and an estimated 165.9 million persons were a part of "BPL-families-with-a-RSBY-card" (Ministry of Labour and Employment, 2012).…”
Section: Introductionmentioning
confidence: 99%